Práticas pedagógicas na alfabetização da criança com deficiência intelectual - Silva, Andrialex William da (2020)
Contemporary society is permeated with written language in its most different forms. In daily life’s various actions, reading and writing skills are often required, therefore the teaching of written language is an utmost question for a contemporary school. It is substantial to consider that every individual has the possibility of reading and writing, thus the school must enable the student’s participation in the process of beginning literacy, specially the student with intellectual disability (ID). Such student is often stigmatized and marginalized in social practices and in the schooling process. For that matter, this work has a main goal to analyze the pedagogical practices in the process of beginning literacy of a child with intellectual disability. Specific goals are to investigate the different factors which influence the pedagogical practices developed in the process of beginning literacy of a child with ID; and to describe the professional and personal pathway of the teacher in the scope of pedagogical practices with students with ID. We performed a qualitative case study which dialogues with the participative and ethnographic research. The research field was a third-grade group of Elementary School students of a philanthropic school located in the West Zone of Natal – RN/Brazil. The group that belonged to teacher Conceição, main participant in the study, had seventeen children, being one of them a child with intellectual disability. When investigating the pedagogical practice in the process of beginning literacy, we verified that different factors have influenced her, such as the physical and social location of the educational institution, the socioeconomic and learning profile of the students, as well as the teacher’s own life story and career. Regarding the pedagogical practice, we understand it as subcategorized in three moments: the planning, the execution and the evaluation. In our investigation, w checked that the phonic method pervades the moments in pedagogical practices which aims at the teaching of written language, additionally, we identified moments of curricular flexibilization centered at the student with ID. We understood that the pedagogical practice which aims at the beginning literacy of a student with ID needs, essentially, to consider the abilities and potential of the student, however respecting their singularities.